Emerging strategy for eco-friendly management of black pepper root-knot nematodes - Nguyen, Van Bon; Wang, San Lang; Nguyen, Thi Hanh; Nguyen, Anh Dzung (Vietnam Journal of Science and Technology, 2023)
Black pepper is one of the most important industrial crops with high economic value for export. This crop is planted in Vietnam, Indonesia, India, and Brazil. Vietnam is the largest producer and exporter of peppercorns. This crop is widely cultivated in the Central Highlands and southeastern areas, with about 124,500 hectares, producing the largest amount of black peppercorns at 193,300 tons per year. However, the cultivation of this plant has faced various pathogen diseases, including the root–knot nematodes (RKNs). For years, many methods have been investigated for managing this disease. Especially in recent years, the number of studies on screening and utilization of beneficial microbes and their active secondary metabolites for effective treatment of RKNs has increased and is also recognized as an emerging research topic. In this review, we discuss and emphasize the significant research results concerning this novel strategy for the effective management of black pepper root-knot nematodes, as well as future studies in this direction. This review provides complete scientific information which may be useful for further investigation of sustainable cultivation of black pepper crops.Keywords: Black pepper, root–knot nematodes, beneficial microbes, nematocidal compounds, microbial fermentation.